Pembedahan Robotik Menggunakan Adept Cobra - Ayob, Mohd Nasir (Universiti Sains Malaysia, 2006)
Nowadays, the growth of technology field causes the other field to take the advantage. In medical field, robot is assign to assist surgeon in surgery. The project is done to measure the ability of industrial robot to perform the surgery task. The scope of the project includes design and build up the gripper, using the real surgery equipment, prototype skull and write the programming language using Adept V+. Camera is used as the vision sensor system for the robot. The grabbed image from the camera is then being process using V+ programming. One of a major disadvantage of image processing using V+ is the processing time is quite long. So if the camera is set to monitor the distance between centroid and robot while the robot moves is not practical. This is because the system is completely controlled by the Adept controller where the capacity and speed of the processor and RAM are small compared to PC system. The step being used is to capture the image once each time the centroid is interested. The image processing is also being simplified and is sufficient to determine the centroid of the object. Coordinate in image window is converted to millimeter and base on the robot's coordinate system. The limitation of the camera is that it is only capturing image in 2 dimensions while the robot workspace is in 3 dimensions. The camera is meant only to measure distance in 2 dimensions which is X-Y plane. So in z-axis for example, when the robot is moving downward to the object then the distance between the effector is difficult to be measured. Force sensor is used to overcome this problem. The sensor is set to trigger when the force reading exceed the threshold value. Then the robot is set to stop immediately when the robot touch the skull. The limitation of using Adept Cobra in surgery is the articulation of the robot which is the arm cannot be moved diagonally to approach the skull. Because the surface of the skull is not flat then the robot must be able to approach the skull and moving into the drilled hole in perpendicular direction to skull's surface.